Analysis of Learning Difficulties in Renewable and Non-Renewable Energy Sources in Science Subjects for Class III Students at SD It Nur Ihsan Medan - Rizka Hidayah Husin Lubis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine students' abilities in learning renewable and non-renewable energy sources in science subjects and what are the learning difficulties of students in renewable and non-renewable energy sources in science subjects and the factors that cause students' learning difficulties in renewable and non-renewable energy sources in science subjects class III students. In the research used a qualitative approach with the type of case study research, the techniques used were observation and interviews. In the study, it was obtained the value of students' ability to work on Renewable and Non-Renewable Energy Sources questions. In Class III SD IT Nur Ihsan Medan students with an average score of 63 are included in the high criteria with difficulty working on question number 1 with a difficulty percentage of 64%, working on problem number 2 with a difficulty percentage of 68%, working on problem number 3 with a difficulty percentage of 64%. , working on question number 4 with a difficulty percentage of 60% and working on question number 5 with a difficulty percentage of 64%.